MANAJEMEN INOVASI KURIKULUM PENDIDIKAN DASAR DI SEKOLAH DASAR MUHAMMADIYAH PROGRAM KHUSUS SURAKARTA - Masruchan, Masruchan (El-Hayah, 2018)
Abstract  : Along with the development of education, curriculum must be able to adjust. Strategy of maintaining curriculum structure without change and innovation will have an impact on bad quality as well as good quality of education. This research is intended to determine: 1) Arrangement of curriculum innovation at Muhmmadiyah Elementary School Special Program, 2) Concept, process, characteristic, and strategy used in innovation management curriculum at Muhmmadiyah Elementary School Special Program Surakarta, 3) Suppoting and inhibiting factors in making curriculum innovation at Muhmmadiyah Elementary School Special Program Surakarta.This research applied descriptive qualitative method. This research was conducted at Muhmmadiyah Elementary School Special Program Kota Barat Surakarta. Informants of this research were Principal, teachers, staffs, and students. Technique of collecting data used observation, in-depth interview and documentation. Technique of validity data used interactive model, including data reduction, data collection, data display and conclusion. This research shows that: 1)  Muhmmadiyah Elementary School Special Program having Sharia curriculum is the result of modification between national sharia curriculum of KTSP and curriculum 13 by synergizing knowledge and diniyyah (religion) as a guidance in conducting learning process for its curriculum innovation, 2) Learning type of Sharia school curriculum is done by synergizing Sharia’s values inside learning subjects, without adding new material inside sharia school curriculum, 3) Supporting factors in arranging curriculum innovation  at Muhmmadiyah Elementary School Special Program are daily, weekly, and annually events, extracurricular events and integration of special program, i.e. sharia curriculum and other general subjects. Meanwhile, inhibiting factors are difficulties in conducting and implementing curriculum innovation due to neighborhood and advanced technology. The benefits of sharia school curriculum planning may bring  the change among the students to understand Islam and good attitude to create Muslim generation of Ulul Albab                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                    Keywords: innovation, management, curriculum, Muhmmadiyah Elementary School Special Program